2008
DOI: 10.2146/ajhp070225
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic agents for anemia of critical illness

Abstract: Published data suggest a prohibitive cost associated with epoetin alfa use in critically ill patients given that the only well-supported clinical benefit of this treatment is the avoidance of transfusion-related adverse events. Continued research is necessary to clarify if there is a net clinical benefit of epoetin use (especially in trauma patients) and to develop optimal blood management strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Their model assumed that there would be a significant increase in infections associated with blood transfusions. Shermock et al, 29 although using the same data, did not find EPO to be cost‐effective. Chui et al 32 used data from the EPO‐3 trial 30 .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Their model assumed that there would be a significant increase in infections associated with blood transfusions. Shermock et al, 29 although using the same data, did not find EPO to be cost‐effective. Chui et al 32 used data from the EPO‐3 trial 30 .…”
Section: Resultsmentioning
confidence: 92%
“…With an average of 40 000 units per dose, the price of one single dose is around $450 28 . Two studies performed a formal cost‐effectiveness analysis in 2005 27,29 . Both studies predated the largest study of erythropoietin in critically ill patients 30 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Those studies were relatively small, but no adverse outcomes were reported in patients who received ESA therapy . Interestingly, the cost of ESAs was also cited as a limitation to their use in critically ill adult patients with anemia . Further trials are needed to determine whether these approaches are safe and effective for selected pediatric and adult patient populations.…”
Section: Special Considerations For Pediatric Patientsmentioning
confidence: 99%
“…[34][35][36][37][38] Interestingly, the high cost of ESAs was also noted as a significant limitation to their use in critically ill adult patients with anemia. 39 Further studies are needed to determine whether these approaches are safe and effective for selected pediatric and adult patient populations.…”
Section: Special Considerations For Pediatric Patientsmentioning
confidence: 99%